2019
DOI: 10.21203/rs.2.11481/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Patient-level factors influencing hypertension control in adults in Accra, Ghana

Abstract: Background : Effective control of blood pressure is necessary to avert the risk of cardiovascular diseases from uncontrolled hypertension. Despite evidence on the benefits of hypertension control, rates of control in Ghana remain low. This study assessed the patient-level factors that influence hypertension control among adults in Accra, Ghana. Methods: A total of 360 hypertensive patients from two hospitals in Accra, Ghana were enrolled in the study. Client socio-demographic characteristics were tabulated an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(3 reference statements)
1
0
0
Order By: Relevance
“…Over three-quarters (78.8%) had a family member who died of hypertension, with a comparable proportion either being a mother (37.7%) or sibling (36.6%). These findings were similar with the study conducted in Ghana which showed respondents were mostly married with ages ranging from 27 to 94 years (Okai et al, 2020).…”
Section: Patient Socio-demographic Characteristicssupporting
confidence: 91%
“…Over three-quarters (78.8%) had a family member who died of hypertension, with a comparable proportion either being a mother (37.7%) or sibling (36.6%). These findings were similar with the study conducted in Ghana which showed respondents were mostly married with ages ranging from 27 to 94 years (Okai et al, 2020).…”
Section: Patient Socio-demographic Characteristicssupporting
confidence: 91%